Odpowiedzi

Najlepsza Odpowiedź!
2009-12-06T19:51:40+01:00
Zapisz w postaci sumy algebraicznej:
a) (2a+b) * c - (2ac - bc +1) =
=2ac+bc-2ac+bc-1=
=2bc-1

b) 5(x - z ) +2(z - x) =
=5x-5z+2z-2x=
=3x-3z

c) 2x²(x - 5)-3x(x² - 3x+5)=
=2x³-10x²-3x³+9x²-15x=
=-x³-x²-15x

d)6( a² + b + ⅓) - 6( a² - ½) - 3 ( b +⅓)=
= 6 a² + 6b + 2- 6a² +3 - 3 b -1=
=3b+4
2009-12-06T19:51:52+01:00
Witaj:)
a) (2a+b) * c - (2ac - bc +1) =
2ac+bc-2ac+bc-1 = 2bc-1
b) 5(x - z ) +2(z - x) =
5x-5z+2z-2x = 3x-3z
c) 2x²(x - 5)-3x(x² - 3x+5)=
2x³-10x²-3x³+9x²-15x = -x³-x²-15x
d)6( a² + b + ⅓) - 6( a² - ½) - 3 ( b +⅓)=
6a²+6b+2-6a²+3-3b-1= 3b+4
2009-12-06T19:56:20+01:00
A) (2a+b) * c - (2ac - bc +1) = 2ac+bc-2ac+bc-1=2bc-1
b) 5(x - z ) +2(z - x) =5x-5z+2z-2x=3x-3z
c) 2x²(x - 5)-3x(x² - 3x+5)= 2xsześcian- 10xkwadrat- 3xsześcian+ +9xkwadrat-15x=-xsześcian-xkwadrat
d) 6( a² + b + ⅓) - 6( a² - ½) - 3 ( b +⅓)= 6a kwadrat +6b +2- 6a kwadrat + 3 -3b -1= 3b+5